How well are Brazilian mastologists (breast surgeons) trained in breast reconstruction and oncoplastic surgery? A study of the impact of a breast reconstruction and oncoplastic surgery improvement course - Businaro Fernandes João, Thais; de Oliveira, Vilmar Marques; Bagnoli, Fábio; Bastos, Maria Carolina Soliani; Rinaldi, José Francisco; Brenelli, Fabrício Palermo; Mateus, Evandro Fallaci (Frontiers in Oncology, 2023)
Introduction The breasts are a female symbol, impacts self-image and self-esteem. Breast reconstructive and oncoplastic surgeries have an important role in minimizing injuries. In Brazil less than a third of public health system (SUS) users have access to immediate reconstructive surgery. The low rate of breast reconstructions has multiple causes and the deficiency in availability and surgeons’ technical qualification play a role. In 2010, the Breast Reconstruction and Oncoplastic Surgery Improvement Course was created by professors of the Mastology Department of Santa Casa de São Paulo and State University of Campinas (UNICAMP). The objectives of this study were to evaluate the impact of the techniques learned on patients’ management by the surgeons enrolled in the Course, as well as to characterize their profile. Methods All students enrolled in the Improvement Course between 2010 and 2018 were invited to answer an online questionnaire. Students who did not agree to answer the questionnaire or answered them incompletely were excluded. Results Total students included: 59. The mean age: 48.9 years, male (72%) with more than 5 years of Mastology practice (82.2%), from all regions of Brazil, 1.7% from the North, 33.9% from the Northeast, 44.1% from the Southeast, and 12% from the South. Most of the students considered they had little or no knowledge of breast reconstruction (74.6%) and 91,5% did not consider they had enough aptitude to perform breast reconstructions after finishing residency. After the Course, 96.6% considered themselves apt to perform such surgeries. Over 90% of the students considered the Course had impacted their practice and changed their surgical strategy view. Before the Course, 84.8% of the students stated that less than half of their patients who were operated on for breast cancer had breast reconstruction, compared to 30.5% after the Course. Conclusion The Breast Reconstruction and Oncoplastic Surgery Improvement Course studied here positively impacted the mastologists’ management of patients. New training centers worldwide can help a lot of women with breast cancer.